2020
DOI: 10.1002/pmrj.12357
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Early Versus Delayed Physical Rehabilitation on In‐Hospital Mortality in Interstitial Pneumonia: A Retrospective Cohort Study

Abstract: Introduction Although early rehabilitation for acute inpatients is widely recommended, the effectiveness of early physical rehabilitation for interstitial pneumonia in the acute setting remains unclear. Objective To investigate the impact of early rehabilitation on mortality in patients with interstitial pneumonia in the acute setting. Design Retrospective cohort study used a hospital‐based database created by the Japan Medical Data Center. Setting Over 100 acute‐care hospitals across Japan. Participants Inpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“… 2 Studies have shown that early rehabilitation interventions for community-acquired pneumonia and interstitial pneumonia within 2 days of admission reduced in-hospital mortality. 26 , 27 The two primary objectives of rehabilitation in this stage are promoting airway clearance and preventing complications of acute illness-related immobilization.…”
Section: Suggestions For Rehabilitation Of Hospitalized Patients Withmentioning
confidence: 99%
“… 2 Studies have shown that early rehabilitation interventions for community-acquired pneumonia and interstitial pneumonia within 2 days of admission reduced in-hospital mortality. 26 , 27 The two primary objectives of rehabilitation in this stage are promoting airway clearance and preventing complications of acute illness-related immobilization.…”
Section: Suggestions For Rehabilitation Of Hospitalized Patients Withmentioning
confidence: 99%
“…Data are currently still being added to the database. 4. In order to protect personal information, data from medical institutions are collected as information that has been anonymized in accordance with Clause 2:9 of the Law for the Protection of Personal Information, on the basis of a personal ID for each medical institution with which individuals cannot be identified.…”
Section: Jmdc Provides Services Of Aggregating and Analyzing Clini-mentioning
confidence: 99%
“…Research carried out using this database includes the following: Factor analysis of outcome 3‐4 Patient characteristics 5‐6 Validations of indices 7 …”
Section: Data Resource Basicsmentioning
confidence: 99%